Protocol for validating liquid-liquid phase separation as a driver of membraneless organelle assembly in vitro and in human cells - Marius Hedtfeld; Andrea Musacchio (STAR Protocols)
Summary: Liquid-liquid phase separation (LLPS) of scaffold proteins has often been proposed to drive the biogenesis of membraneless cellular compartments. Here, we present a protocol to link in vitro LLPS propensity to localization in vivo. We describe steps for examining LLPS in vitro in the presence of crowding agents or cytomimetic media. We complement our in vitro studies with recombinant proteins with experiments of protein electroporation into mitotic HeLa cells. In addition, we discuss steps to assess protein localization and delivery levels.For complete details on the use and execution of this protocol, please refer to Hedtfeld et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.